The Influence Of Perception, Knowledge, And Skills On Employee Performance In The Population Control And Family Planning Service Of Binjai City (A Case Study Of The Use Of Digital Transformation) - Nayla Putri Aliska; Saimara A.M Sebayang; Muhammad Toyib Daulay (Journal of Management, Economic, and Accounting, 2026)
This study examines the influence of Perception, Knowledge, and Skills on Employee Performance at the Population Control and Family Planning Agency (DPPKB) of Binjai City. Using an associative quantitative approach with 35 permanent employees, data were collected through Likert-scale questionnaires, observations, and interviews, and analyzed using multiple linear regression in SPSS 23. The results indicate that Perception, Knowledge, and Skills each have a positive and significant effect on employee performance, and together explain 78.8% of the performance variation (R² = 0.788). The findings highlight the importance of enhancing perception, knowledge, and skills through training and competency development to optimize employee performance.